Uniportal VATS Treatment of Giant Bullous Emphysema: Is It Safe and Effective? - Antonio Giulio Napolitano; Khrystyna Kuzmych; Claudia Bellettati; Giuseppe Calabrese; Adriana Nocera; Maria Letizia Vita; Mahmoud Ismail; Maria Teresa Congedo; Elisa Meacci; Stefano Margaritora; Dania Nachira (Surgeries)
Background: Emphysema is a chronic lung disease characterized by alveolar wall destruction, leading to impaired gas exchange. Giant bullous emphysema (GBE) is a severe form of emphysema, often requiring surgical intervention. Video-assisted thoracoscopic surgery (VATS) is a minimally invasive approach for various thoracic pathologies, including lung volume reduction surgery (LVRS) and bullectomy for emphysematous bullae. Uniportal VATS (U–VATS), a further refinement, offers benefits such as reduced postoperative pain and faster recovery. Methods: This retrospective study analyzed data from two high-volume European Thoracic Surgery centers between August 2016 to January 2024. A total of 29 patients underwent U–VATS bullectomy for GBE. Results: Nineteen patients were males (65.5%) with a mean age of 44.7 ± 8.8 years. Ten (34.5%) were active smokers. Eighteen patients (62.1%) presented with a single giant bulla, while the remaining cases were in the context of pulmonary emphysema. Four patients (13.8%) presented with pneumothorax, with one requiring preoperative chest drainage. Twenty-eight patients (96.6%) underwent only U–VATS bullectomy, with additional chemical pleurodesis in eleven cases (37.9%). One patient (3.4%) underwent a left upper lobectomy for a giant bulla and NSCLC. In cases of severe lung emphysema and fragile pulmonary tissue, the stapler line was buttressed with Gore® Seamguard®. No conversions to thoracotomy, postoperative air-leaks, or major complications were recorded. At a mean follow-up time of 22.0 ± 14.0 months, no pneumothorax recurrence was documented. At about six months after surgery, pulmonary function significantly improved. Conclusions: U–VATS bullectomy appears to be a safe and feasible technique for the treatment of bullae in GBE, offering promising postoperative outcomes.